LA MILITANCIA DE ABOGADOS EN DEFENSA DE LOS DERECHOS HUMANOS A PARTIR DE LA ÚLTIMA DICTADURA MILITAR EN ROSARIO. ANTECEDENTES, PARTICIPACIÓN Y PERTENENCIAS IDENTITARIAS - SCOCCO, MARIANELA (Universidad Nacional del Litoral, 2017)
This article focuses on the analysis of the lawyer’s militancy in defending the human rights during the last dictatorship (1976-1983) and in the first years of democracy. However, we will focus on the changes of the lawyer’s profile who had dedicated to this activity. We identify a process that started with the firsts lawyers who had defended the first detainees held for political and guild reasons since the mid 1930- specially the second half of the XX century- to the establishment of the last dictatorship, in 1970. The main objective is to study these social and political actors and the associations in which they had participated: we will analyze their circulation, it is to say, their double or multiple political membership. We will focus on the case of the city of Rosario and we will take as an example the case of two lawyers who had dedicated to the human rights defense by taking part in different organizations of the city.